Urinary P75: a promising biomarker for amyotrophic lateral sclerosis - Martin R Turner; Andrea Malaspina; Pamela J Shaw; Stephanie Shepheard; Nick Verber; Mary-Louise Rogers; Laura R Chapman (BMJ Neurology Open)
Background Amyotrophic lateral sclerosis (ALS) is a progressive and fatal disease. The urinary neurotrophin receptor p75 extracellular domain (p75ECD) has previously been reported as a potential disease biomarker for diagnosis, severity assessment and monitoring therapeutic response.Methods This study measured urinary p75ECD using an enzyme-linked immunoassay and normalised the results against urinary creatinine. Participants were recruited via A Multicentre Biomarker Resource Strategy in ALS (AMBroSIA) programme. Study participants included 97 ALS patients, 24 of whom were studied longitudinally, and 27 healthy controls. The study focused on urinary p75ECD and its potential association with different subtypes of ALS, change over time, disease progression, severity of symptoms and survival from symptom onset.Results Confirming previous findings, urinary p75ECD levels were significantly higher in patients with ALS (median 6.78 ng/mg, 95% CI (5.12 to 9.23)) compared with controls (4.57 ng/mg, 95% CI (3.35 to 5.89)) at first study visit. There was a significant negative correlation between absolute change in the Revised ALS Functional Rating Scale score and p75ECD levels (Spearman’s rho=−0.371, p≤0.0004, 95% CI (−0.543 to –0.169)), indicating that an increase in the severity of motor neuron injury correlated with an increase in p75ECD levels. There was a significant increase in p75ECD between first and second samples in the same participants, indicating an increase in the level of this biomarker longitudinally during the disease course (moderate effect size of −0.3).Conclusions Urinary p75ECD is a promising candidate as a biomarker, which increases with disease progression and has the potential to serve as a pharmacodynamic biomarker.